Gaining Education Character Based on Cultural Sundanese Values: The Innovation of Islamic Education Curriculum in Facing Era Society 5.0 - Hisny Fajrussalam; Agus Salim Mansyur; Qiqi Yuliati Zaqiah (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This research was motivated by moral and social crises that occur in Indonesian society, especially in West Java. It was predicted that the society is not ready to face this era if they analyse moral cases occur in West Java. Most people who adhere to this religion of Islam, have not been able to fully realize the Islamic values​ in daily life. Ideally, education as a mediator in dealing with these cases presents a solution. Therefore, this article was to provide a basic inspiration regarding the innovation of the Islamic education curriculum based on the values ​​of Sundanese cultural characters. This research uses library research’s method by using inductive-deductive analysis as well as a comparison of literature and content analysis techniques. The result showed that the presence of an Islamic education curriculum based on cultural Sundanese character values ​​could emerge a generation that upholds culture and Islam. Hence, it could make the next generation of a nation to have noble character. Keywords: Sundanese Culture, Era Society 5.0, Curriculum, Islamic Education